Biomarkers of mature neuronal differentiation and related diseases - Xiaodong Yuan; Wen Li; Qi Yan; Ya Ou; Qingxi Long; Pingshu Zhang (Future Science OA)
The nervous system regulates perception, cognition and behavioral responses by serving as the body's primary communication system for receiving, regulating and transmitting information. Neurons are the fundamental structures and units of the nervous system. Their differentiation and maturation processes rely on the expression of specific biomarkers. Neuron-specific intracellular markers can be used to determine the degree of neuronal maturation. Neuronal cytoskeletal proteins dictate the shape and structure of neurons, while synaptic plasticity and signaling processes are intricately associated with neuronal synaptic markers. Furthermore, abnormal expression levels of biomarkers can serve as diagnostic indicators for nervous system diseases. This article reviews the markers of mature neuronal differentiation and their relationship with nervous system diseases.